Better ways to green-light new projects : organizations can make better choices about which R&D projects gain funding by managing bias and involving more people - Grohsjean, Thorsten; Dahlander, Linus; Salter, Ammon J.; Criscuolo, Paola (MIT Sloan Management Review, 2021)
Relying on expert panels to judge which innovation projects should get the go-ahead for funding produces mixed results. The authors' study of how R&D projects are green-lighted reveals multiple flaws in the process that can result in biased and poor decisions. The article details potential problems and suggests alternative ways that companies can review and decide on new projects. These newer approaches are aimed at mitigating bias and often involve engaging a wider variety of perspectives.